Glucose prevents the fall in ventromedial hypothalamic GABA that is required for full activation of glucose counterregulatory responses during hypoglycemia - Zhu, Wanling (American Physiological Society, 2010)
Local delivery of glucose into a critical glucose-sensing region within the brain, the ventromedial hypothalamus (VMH), can suppress glucose counterregulatory responses to systemic hypoglycemia. Here, we investigated whether this suppression was accomplished through changes in GABA output in the VMH. Sprague-Dawley rats had catheters and guide cannulas implanted. Eight to ten days later, microdialysis-microinjection probes were inserted into the VMH, and they were dialyzed with varying concentrations of glucose from 0 to 100 mM. Two groups of rats were microdialyzed with 100 mM glucose and microinjected with either the K(ATP) channel opener diazoxide or a GABA(A) receptor antagonist. These animals were then subjected to a hyperinsulinemic-hypoglycemic glucose clamp. As expected, perfusion of glucose into the VMH suppressed the counterregulatory responses. Extracellular VMH GABA levels positively correlated with the concentration of glucose in the perfusate. In turn, extracellular GABA concentrations in the VMH were inversely related to the degree of counterregulatory hormone release. Of note, microinjection of either diazoxide or the GABA(A) receptor antagonist reversed the suppressive effects of VMH glucose delivery on counterregulatory responses. Some GABAergic neurons in the VMH respond to changes in local glucose concentration. Glucose in the VMH dose-dependently stimulates GABA release, and this in turn dose-dependently suppresses the glucagon and epinephrine responses to hypoglycemia. These data suggest that during hypoglycemia a decrease in glucose concentration within the VMH may provide an important signal that rapidly inactivates VMH GABAergic neurons, reducing inhibitory GABAergic tone, which in turn enhances the counterregulatory responses to hypoglycemia.